Modular MR-compatible lower leg exercise device for whole-body scanners - Hosseini Ghomi, Reza; Bredella, Miriam A.; Thomas, Bijoy J.; Miller, Karen K.; Torriani, Martin (Skeletal radiology, 2011)
Purpose To develop a modular MR-compatible lower leg exercise device for muscle testing using a clinical 3 T MR scanner. Materials and methods An exercise device to provide isotonic resistance to plantar- or dorsiflexion was constructed from nonferrous materials and designed for easy setup and use in a clinical environment. Validation tests were performed during dynamic MR acquisitions. For this purpose, the device was tested on the posterior lower leg musculature of five subjects during 3 min of exercise at 30% of maximum voluntary plantarflexion during 31-phosphorus MR spectroscopy ( 31 P-MRS). Measures of muscle phosphocreatine (PCr), inorganic phosphate (Pi), and pH were obtained before, during, and after the exercise protocol. Results At the end of exercise regimen, muscle PCr showed a 28% decrease from resting levels (to 21.8 ± 3.9  from 30.4 ± 3.0  mM) and the average PCr recovery rate was 35.3 ± 8.3 s. Muscle Pi concentrations increased 123% (to 14.6 ± 4.7 from 6.5 ± 3.3  mM) and pH decreased 1.5% (to 7.06 ± 0.14 from 7.17 ± 0.07) from resting levels. Conclusion The described MR-compatible lower leg exercise was an effective tool for data acquisition during dynamic MR acquisitions of the calf muscles. The modular design allows for adaptation to other whole-body MR scanners and incorporation of custom-built mechanical or electronic interfaces and can be used for any MR protocol requiring dynamic evaluation of calf muscles.